The effect of a brief mindfulness induction on processing of emotional images: an ERP study - Eddy, Marianna D.; Brunye, Tad T.; Tower-Richardi, Sarah; Mahoney, Caroline R.; Taylor, Holly A. (Frontiers in Psychology, 2015)
The ability to effectively direct one’s attention is an important aspect of regulating emotions and a component of mindfulness. Mindfulness practices have been established as effective interventions for mental and physical illness; however, the underlying neural mechanisms of mindfulness and how they relate to emotional processing have not been explored in depth. The current study used a within-subjects repeated measures design to examine if focused breathing, a brief mindfulness induction, could modulate event-related potentials (ERPs) during emotional image processing relative to a control condition. We related ERP measures of processing positive, negative, and neutral images (the P300 and late posterior positivity – LPP) to state and trait mindfulness measures. Overall, the brief mindfulness induction condition did not influence ERPs reflecting emotional processing; however, in the brief mindfulness induction condition, those participants who reported feeling more decentered (a subscale of the Toronto Mindfulness Scale) after viewing the images had reduced P300 responses to negative versus neutral images.